Mutation spectrum of PTS gene in patients with tetrahydrobiopterin deficiency from jiangxi province - Xie, Kang; Zeng, Baitao; Zhang, Liuyang; Chen, Shaohong; Zou, Yongyi; Yuan, Huizhen; Huang, Shuhui; Wang, Feng; Lu, Qing; Liu, Yanqiu; Yang, Bicheng (Frontiers in Genetics, 2022)
Background: Hyperphenylalaninemia (HPA) is the most common congenital disease of amino acid metabolism, which can be mainly classified into phenylalanine hydroxylase (PAH) deficiency and tetrahydrobiopterin (BH4) deficiency. BH4 deficiency (BH4D) is caused by genetic defects in enzymes involved in the biosynthesis and regeneration of BH4. The 6-pyruvoyl-tetrahydropterin synthase (PTPS), which is encoded by PTS gene, is involved in the biosynthesis of BH4. PTPS deficiency (PTPSD) is the major cause of BH4D. The frequency of BH4D was estimated to be nearly 30% among HPA population in Jiangxi, which is much higher than that in the Chinese population on average. This study aims to characterize the mutational spectrum of PTS gene in patients with PTPSD from Jiangxi province. Method: A cohort of fifty-three PTPSD families from Jiangxi was enrolled to analyze PTS gene variants by Sanger sequencing. Results: A total of 106 variants were identified in 106 alleles of fifty- three patients with PTPSD, including fourteen types of variants reported previously, and two novel variants. The predominant variant was P87S(47.2%), followed by IVS1-291A>G(19.8%), N52S(8.5%), D96N(6.6%) and L127F(4.7%). Conclusion: The results of this study could not only provide guidance for molecular diagnosis and genetic counseling of PTPSD, but also enrich the PTS mutation database.